2017
DOI: 10.1038/s41598-017-10382-2
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 fatty acids correlate with gut microbiome diversity and production of N-carbamylglutamate in middle aged and elderly women

Abstract: Omega-3 fatty acids may influence human physiological parameters in part by affecting the gut microbiome. The aim of this study was to investigate the links between omega-3 fatty acids, gut microbiome diversity and composition and faecal metabolomic profiles in middle aged and elderly women. We analysed data from 876 twins with 16S microbiome data and DHA, total omega-3, and other circulating fatty acids. Estimated food intake of omega-3 fatty acids were obtained from food frequency questionnaires. Both total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
113
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(136 citation statements)
references
References 80 publications
7
113
1
6
Order By: Relevance
“…While higher SCFA levels in the stool with fibre‐free EN compared to PN have been reported (Sobotka et al , ; Schneider et al , ), the reason for this is unclear. The EN formula provided also contained omega 3 fatty acids, which have recently been associated with increased abundance of butyrate‐producing bacteria in healthy individuals (Watson et al , ), which may be independent of dietary fibre intake (Menni et al , ). Further investigation of the benefit of fibre and omega‐3 fatty acid‐containing EN on clinical outcomes in HPCT is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…While higher SCFA levels in the stool with fibre‐free EN compared to PN have been reported (Sobotka et al , ; Schneider et al , ), the reason for this is unclear. The EN formula provided also contained omega 3 fatty acids, which have recently been associated with increased abundance of butyrate‐producing bacteria in healthy individuals (Watson et al , ), which may be independent of dietary fibre intake (Menni et al , ). Further investigation of the benefit of fibre and omega‐3 fatty acid‐containing EN on clinical outcomes in HPCT is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…70 In another larger, cross-sectional study with 876 women, Menni et al demonstrated that polyunsaturated fats were associated with an increase in microbial diversity and an increase in members of the Lachnospiraceae family. 71 …”
Section: Environmental Factorsmentioning
confidence: 99%
“…a gold standard profile. Alpha diversity metrics summarize the variety (or richness) and distribution of taxa present in a profile [29] and, among other uses, is commonly used to observe global shifts in community structure as a result of some environmental parameter [30][31][32][33]. The simplest alpha diversity metric is the number of taxa present in a given environment.…”
Section: Alpha Diversity Metricsmentioning
confidence: 99%